On the polyconvolution with the weight function $γ(y)=\cos y$ of Hartley integral transforms $\mathcal H_1,$ $\mathcal H_2,$ $\mathcal H_1$ and integral equations - Khoa, N. M.; Thang, T. V. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 517.5We construct and investigate new polyconvolution with the weight function $γ(y)=\cos y$ of Hartley integral transforms $\mathcal H_1,$ $\mathcal H_2,$ $\mathcal H_1$ and apply it to solve integral equations and a system of integral equations of polyconvolution type.